RICE HOUSEHOLD CONSUMPTION I YOGYAKARTA SPECIAL REGION - Fiska Rahmawati; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Agro Ekonomi, 2013)
This study aims to 1) determine factors that influenced the level of household consumption of rice 2) determinwe the elasticity of demand for rice at the household level, and 3) determine differnes of household rice consumption in rural and urban areas. This study used National Socio-Economic Survey (SUSENAS) data at household level from Central Bureau of Statistic (BPS) in 2011 for Yogyakarta Special Region. About 173 households out of 3200 households in rural and urban areas were chsen as sample in this research. The first and second objectives were analyzed by using OLS method, while the third objective was analyzed by using t-test. The result showed that households rice consumption was influenced by the prices of rice, sweet potato, instant noodles, beef, tempe, number of  members, income, and location of residence. Household consumption of rice in Yogyakarta was positively influenced by the price of instant noodles and the number of household members, but it was negatively affected by the rpice of rice, beef prices, and income. There was a difference between rice consumption in urban and rural areas. Based on the concept of price elasticity, it was known that households rice consumption was inelastic, instant noodles is substitute of rice and beef was complementing rice. The average household rice consumption in rural areas was higher than that of urban households.